Honesty, lemons, and symbolic signals - Jorge M. Streb; Gustavo Torrens (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2012)
Under asymmetric information, dishonest sellers lead to market unraveling in the lemons model. An additional cost of dishonesty is that language becomes cheap talk. We develop instead a model where people derive utility from actions (what they say), as well as from outcomes, so talk is costly. We find that the existence of honest agents that mean what they say is not enough to make trade more likely, unless a traceability condition that prevents arbitrage is met. When we introduce a continuum of misrepresentation cost types and qualities, full market unraveling is not possible and babbling equilibria are eliminated. More generally, costly talk is a special kind of signal, a symbolic signal that presupposes linguistic conventions, otherwise truth and falsehood, as well as misrepresentation costs, are undefined.
Keywords: D8; C7; 330; asymmetric information; honesty; trust; symbols; signals; costly talk; Asymmetrische Information